Why do Children Rape? Some Considerations of Violent Sexual Behavior in Adolescents Qualitative Data from a Scientific Field Study in Buenos Aires - Mora, Marcelo Della (European Scientific Journal, ESJ, 2017)
Adolescents’ discursive characteristics were studied through open interviews. Main issues were: sexuality, sources of sexual information received, violence and violent sexual behavior. Primary data were collected to analyze and compare, from a gender perspective, the discursive productions. In addition, sensitive information was collected from a group of experts from different disciplines related to the subject under study. Objective: to analyze if there is any connection between sexual information received (from school, parents, peers, etc.) in adolescents living in the City of Buenos Aires and violent sexual behavior, in the context of other intervening variables. Methodology: Subjects: Male and female adolescents ages 13 - 19 who were attending school, with residence in the City of Buenos Aires. Sampling: intentional. Instruments for data collection: a) Open individual and group interviews (with a brief guide of explored topics), with adolescents of the mentioned age range and place of residence. b) Open interviews (also with a brief guide of the main explored topics) with key informants, task experts and professions related to the researched subject. c) Updating and deepening the theoretical corpus in indexed databases of scientific journals and international and local events abstracts. These methodological strategies were very useful to develop a Measurement Instrument (Pilot Survey) that contemplates variables of two broad categories under study: Sexual Information and Violent Sexual Behavior-in addition to other sociodemographic, educational, family and attitudinal variables-whose indicators will allow us to measure the phenomenon under study, and will be applied and analyzed in the next qualitative-quantitative stage of the research. Results: Violent sexual behavior appears to be related to the sexual information received.